The Relationship Between Sports And Sleep Quality of Students of The Faculty of Health Sciences, Singaperbangsa University, Karawang - Mochamad Sandy Yusuf; Muhammad Irsyad; Syahrul Darmawan; Muhammad Arief Setiawan (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to analyze the effect of exercise on the sleep quality of students at the Faculty of Health, Singaperbangsa University, Karawang. Good sleep quality is essential for physical and mental health, but many students experience sleep problems due to high academic demands and modern lifestyles. The research method used was comparative, involving 17 students who filled out a questionnaire regarding the frequency, intensity, and duration of exercise and their sleep quality. The results showed that 70.6% of respondents felt an improvement in sleep quality after exercising, especially with light physical activity such as jogging for 30 minutes. This study also found that exercise helps reduce stress levels and increases the production of hormones that support better sleep. Thus, it is recommended that students integrate exercise routines into their lifestyles to improve sleep quality and overall well-being. This study provides important insights into the benefits of exercise not only for physical health but also for mental health and encourages educational institutions to support sports activities among students.